Benefits of employee assistance programmes in industrial organisations (2016)
Ensuring that employees work with their greatest potential to enhance productivity and efficiency are inhibited and restricted by physical and psychological problems. These problems come in the form of depression, sickness, disability, stress, burnout, absenteeism, and presenteeism. Work organisations can reduce or eliminate these problems through employees assistance programme (EAP). EAP typically provides screening, assessment, brief intervention, referrals to other services, and case managements with longitudinal follow up for these problems. This paper looked at the historical evolution of EAPs, functions of EAPs, the need for the establishment of EAPs in the workplace and the main types of EAPs which are classified based on the users, namely: individual, managerial/supervisory, organisational and administrative services. The paper also looked at the roles of EAPs to individual, managers and the organization. The paper established that EAP practitioners provide consulting services to managers and supervisors regarding employee performance and serve as behavioural consultants to corporate leaders when unexpected events occur. It helps employees to obtain help with problems that can/are affecting work, family and their well-being. Early uses of EAPs contributed to the prevention of serious problems for the individual employee, family and employer. Finally, positive organizational culture, improved morals, attraction of top talents, increased job commitment and increased job satisfaction are guaranteed when EAPs are efficiently and effectively utilised. It is recommended that the identification, integrating EAPs will enhance employees and workplace effectiveness in becoming vital tool for maintaining and improving worker health and productivity, retaining valued employees, and returning employees to work after illness or injuries. Furthermore, the establishment of EAPs will confer the following benefits to the organisation: productive employees, low rate of absenteeism, better job climates and organisational morale, less inter-group conflicts.